2017
DOI: 10.1089/jpm.2016.0465
|View full text |Cite
|
Sign up to set email alerts
|

Drainage Percutaneous Endoscopic Gastrostomy for Malignant Bowel Obstruction in Gastrointestinal Cancers: Prognosis and Implications for Timing of Palliative Intervention

Abstract: We found that prognosis following diagnosis of MBO in patients with gastrointestinal malignancies remains poor. Our data suggest that timing of dPEG placement in MBO does not affect OS and, therefore, earlier intervention with this procedure may allow earlier and prolonged palliative relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
1
9
0
2
Order By: Relevance
“…Alternatives to surgery such as venting gastrostomy tubes and stents, while having fewer complications, are typically used in patients who have poor performance status and likely would not tolerate surgery. 19,20 In our study, those treated with gastrostomy tubes uniformly had the worst outcomes in terms of length of stay, mortality, and survival compared to those treated with stents, surgery, and medical management. Similarly, Lilley et al 5 reported that patients with IO from pancreatic and ovarian cancer treated with venting gastrostomy tubes had shorter survival (median: 38 vs 128 days) and higher 30day mortality (43% vs 18%) compared to those undergoing surgery.…”
Section: Discussionmentioning
confidence: 63%
“…Alternatives to surgery such as venting gastrostomy tubes and stents, while having fewer complications, are typically used in patients who have poor performance status and likely would not tolerate surgery. 19,20 In our study, those treated with gastrostomy tubes uniformly had the worst outcomes in terms of length of stay, mortality, and survival compared to those treated with stents, surgery, and medical management. Similarly, Lilley et al 5 reported that patients with IO from pancreatic and ovarian cancer treated with venting gastrostomy tubes had shorter survival (median: 38 vs 128 days) and higher 30day mortality (43% vs 18%) compared to those undergoing surgery.…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, PEG insertion is preferable for patients who are required to maintain enteral feeding for a long period, because the quality of life should be considered 14 . As the indications for PEG insertion expand, patients who require continuous drainage for malignant bowel obstruction also undergo PEG to drain gastric fluid and resolve nausea or vomiting 15,16 . There is an increasing number of patients undergoing PEG insertion for such reasons, and many research studies relating to the procedure have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…PEG tube placement for gastric decompression has also been described as a feasible palliative option for patients with malignant bowel obstruction, but is often associated with higher risk of complications and poor prognosis (38,59,60).…”
Section: Gastric Decompressionmentioning
confidence: 99%